Pembuatan Film Pendek “Hidup Mahasiswa Yang Berubah” Dengan Teknik Cinematografi dengan “One-Take” dan Colorgrading - Rhenal Ahmad Syam; Agusdi Syafrizal; M. Zainul Rahman (JURNAL VOKASI TEKNIK, 2024)
The short film "Hidup Mahasiswa yang Berubah" tells the story of a student who misuses technology. Cinematography, which is the art of capturing moving images, has evolved through technological advancements that have enabled the development of various visual styles and creative techniques. In the short film, cinematography, one-take technique, and color grading are crucial, and how all of these are utilized is essential. Using the Multimedia Development Life Cycle (MDLC) method, the film development consists of six stages: concept, design, material collection, production, testing, and distribution, where one-take and cinematography are applied during the production stage. The film testing was conducted through a questionnaire with 20 students from Polytechnic of Samarinda. The results showed that the one-take technique increased audience engagement, while color grading enhanced the visual and emotional narrative. In summary, a work that is entertaining and visually and emotionally profound is created through creative cinematography, effective one-take technique, and color grading. This provides practical guidance for those just starting to make short films